2011
DOI: 10.1002/ceat.201100330
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Coagulant from Acacia mearnsii de Wild for Wastewater Treatment

Abstract: A novel coagulant agent from Acacia mearnsii de Wild tannin extract was characterized for removal of the anthraquinonic colorant Alizarin Violet 3R and the anionic surfactant sodium dodecylbenzene sulfonate. This coagulant is the result of a previous optimization study. The influence of operative variables such as temperature, coagulant dosage, initial pollutant content, and pH was investigated. The new coagulant demonstrates a high affinity for dye and surfactant and is efficient within a wide range of workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…At acidic pH, it is observed the cationic form of the pollen, which should be higher at acidic pH and lower at basic level. The electrostatic attraction between pollen cationic chains and negatively charged anions in the dye molecules, was then reinforced and the links to hydrophobic chains were enhanced [53]. At neutral pH, relatively low adsorption of AR88 by pollen was observed because HO − could compete with the dye anions for sorption sites [54].…”
Section: Influence Of Ph Variationmentioning
confidence: 99%
“…At acidic pH, it is observed the cationic form of the pollen, which should be higher at acidic pH and lower at basic level. The electrostatic attraction between pollen cationic chains and negatively charged anions in the dye molecules, was then reinforced and the links to hydrophobic chains were enhanced [53]. At neutral pH, relatively low adsorption of AR88 by pollen was observed because HO − could compete with the dye anions for sorption sites [54].…”
Section: Influence Of Ph Variationmentioning
confidence: 99%
“…These mathematical approaches are called adsorption-like coagulation models, and we have previously reported their use (Sánchez-Martín et al, 2011;. However, it is possible to adopt a theoretical proposal based on the surfactant-polymer interaction models.…”
Section: Theoretical Adsorption-like Coagulation Modelmentioning
confidence: 99%
“…A. dealbata was first introduced in Europe in 1816 for horticultural and floricultural purposes (in Portugal, 1850), although in 1999 it was officially listed as invasive [12]. Several authors point out the successful use of coagulants derived from different subspecies of the plant Acacia to treat wastewater [13][14][15][16][17]; therefore, A. dealbata leaves could provide a good product for CFD processes, although, to our knowledge, no studies on this have been reported. Therefore, two environmental problems are addressed in this work: the treatment and control of WW via A. dealbata dissemination.…”
Section: Introductionmentioning
confidence: 99%